STUDI LITERATUR MENGENAI KOMUNALISME LOKAL DENGAN IDEOLOGI NEGARA DALAM POLITIK DEMOKRASI - Pingky Monica Hasugian; Halimah, Martua Felix Jonatan Simanullang, Mira Cahya, Mutiara Fadhilatul Jannah (ADMIN: Jurnal Administrasi Negara, 2024)
This article tries to reveal the dynamics of communism in the history of the nation in Indonesia and the political state examines it within the framework of philosophical thought. Communism is based on the ideas of kinship, regionalism, religion, tribal identity, and others as binding and motivating each individual to put society first before his own interests as an individual. Communalism is closely related to public policy because of the existence of communalism in the political system. Always acting in the name of the public interest in forming political policies and communism requires the obedience of all citizens in its implementation. General community policy in Indonesia does not represent everyone's awareness of their rights and responsibilities, but represents the identity of the community, so that who becomes the leader and figure of the community determines the general order.